Defining sex-based discrimination among strife between the Justice Department and the EEOC. Issue 3 (September 2019) - Ruszkowski, Kelsey R
In the last few decades, US Supreme Court rulings have made strides for the advancement of the LGBT community. However, this community has yet to enjoy equality in the workplace due to its exclusion from Title VII protection. This article details the recent conflict between the Equal Employment Opportunity Commission (EEOC) and the Department of Justice in interpreting Title VII and how this conflict may make it difficult for the Supreme Court to reach a broad ruling concerning sex discrimination under Title VII. The EEOC relies on Supreme Court precedent concerning sex stereotyping to extend Title VII protection to sexual orientation while the Justice Department employs a textualist argument to support a narrow interpretation of sex. However, changing societal norms and advancing neuroscientific research support the conclusion that sexual orientation, gender identity, and expression is included under "sex" even when using textualism to interpret Title VII. Given that the Supreme Court is unlikely to defer to the EEOC's interpretation, these arguments stemming from the social sciences may provide the support the Court needs to justify a decision to end employment discrimination against the LGBT community and gender nonconformists in a way that is consistent with the positions of both the EEOC and the Justice Department.